Sins of Omission and the Practice of Economics - Akerlof, George A. (Journal of Economic Literature, 2020)
This paper advances the proposition that economics, as a discipline, gives rewards that favor the “hard” and disfavor the “soft.” Such bias leads economic research to ignore important topics and problems that are difficult to approach in a “hard” way—thereby resulting in “sins of omission.” This paper argues for reexamination of current institutions for publication and promotion in economics—as it also argues for greatly increased tolerance in norms for publication and promotion as one way of alleviating narrow methodological biases. (JEL A11, B40)